Exchange rates, remittances, and competitiveness in Haiti - Díaz-Bonilla, Eugenio; Paz, Florencia; Piñeiro, Valeria (International Food Policy Research Institute, 2021)
The exchange rate (ER) is one of the most important macroeconomic variables in the economy, defining the price of the domestic currency in relation to a foreign currency or currencies. The level and changes (both actual and expected) of the ER (nominal and real, defined below) have wide influence throughout the economy, affecting and being affected by the demand and supply of traded and nontraded goods and services, the demand and supply of money and monetary assets denominated in local currency in comparison with assets denominated in other currencies, and inflows or outflows of capitals and remittances, among main key variables. In consequence, the ER and ER policies influence growth, employment, inflation, international trade, and banking and fiscal stability (a classical general treatment can be found in Krueger 1983; see also Corden 1990).